2005
DOI: 10.1021/ja051977c
|View full text |Cite
|
Sign up to set email alerts
|

Direct Fabrication and Harvesting of Monodisperse, Shape-Specific Nanobiomaterials

Abstract: A versatile "top-down" method for the fabrication of particles, Particle Replication In Nonwetting Templates (PRINT), is described which affords absolute control over particle size, shape, and composition. This technique is versatile and general enough to fabricate particles with a variety of chemical structures, yet delicate enough to be compatible with sophisticated biological agents. Using PRINT, we have fabricated monodisperse particles of poly(ethylene glycol diacrylate), triacrylate resin, poly(lactic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
680
0
10

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 781 publications
(691 citation statements)
references
References 31 publications
1
680
0
10
Order By: Relevance
“…Microfluidics was revolutionary for paving the way to unprecedented control over size dispersity, shape anisotropy and structure complexity of particles. A novel or improved technique [453][454][455] inheriting abilities of microfluidics but overcoming its problems such as tedious device preparation and scalability would be another renaissance for particle production. Finally, unique mechanical, packing and assembly properties of nonspherical particles are already drawing attention [6,85,161,[453][454][456][457][458][459][460][461][462][463][464][465][466][467][468] but the effect of porosity on such regular nonspherical particles is still waiting to be further exploited.…”
Section: Discussionmentioning
confidence: 99%
“…Microfluidics was revolutionary for paving the way to unprecedented control over size dispersity, shape anisotropy and structure complexity of particles. A novel or improved technique [453][454][455] inheriting abilities of microfluidics but overcoming its problems such as tedious device preparation and scalability would be another renaissance for particle production. Finally, unique mechanical, packing and assembly properties of nonspherical particles are already drawing attention [6,85,161,[453][454][456][457][458][459][460][461][462][463][464][465][466][467][468] but the effect of porosity on such regular nonspherical particles is still waiting to be further exploited.…”
Section: Discussionmentioning
confidence: 99%
“…PRINT provides superior control over particle geometry and physical properties by taking advantage of a novel soft lithographic technique for particle fabrication. This results in low batch-to-batch variability with very low polydispersity values (29,30). Recent work has demonstrated that the PK of PRINT nanoparticles can be carefully and reproducibly calibrated by adjusting the density of PEG chains present on the surface (31).…”
Section: Introductionmentioning
confidence: 99%
“…5,17 In order to elucidate a complete set of design criteria for maximizing selectivity at the cell and tissue levels, synthesis methods need to afford independent control over the physicochemical properties of the resulting particles. A variety of versatile top-down particle fabrication techniques have emerged in the past few decades, chief among them microuidics, 18 lithography, 19 electrospraying, 20 template stretching, 21,22 or combinations thereof. 23,24 However, not all techniques can freely access the material composition, particle architecture, or length scale (#10 mm) relevant to biological assays, especially cellular uptake, and intravenous injections.…”
Section: Introductionmentioning
confidence: 99%